2017
DOI: 10.12799/jkachn.2017.28.2.216
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self-care Behaviors, Empowerment and Social Support on Glycosylated Hemoglobin in Patients with Type 2 Diabetes

Abstract: Purpose:The purpose of the study was to analyze the effects of self-care behavior, empowerment, and social support on glycosylated hemoglobin in patients with type 2 diabetes. Methods: The data were collected during the period of July 1 to July 31, 2016. In total, 172 participants were recruited from outpatients who had been diagnosed with type 2 diabetes at a health care center, a health promotion center at National Health Insurance Corporation, and a tertiary hospital. Statistical data were analyzed with SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
2
5
1
Order By: Relevance
“…This finding is similar to those of previous studies, in which self‐care was shown to have a direct effect on subjective health status (Bishwajit et al, 2017; Jung et al, 2015; Lee & Kim, 2017; Park, 2010). Additionally, we found diabetes self‐care activities to have significant direct and total effects on HbA1c level; this result is also consistent with those of previous studies (Jung et al, 2015; Khairnar et al, 2019; Oh & Lee, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is similar to those of previous studies, in which self‐care was shown to have a direct effect on subjective health status (Bishwajit et al, 2017; Jung et al, 2015; Lee & Kim, 2017; Park, 2010). Additionally, we found diabetes self‐care activities to have significant direct and total effects on HbA1c level; this result is also consistent with those of previous studies (Jung et al, 2015; Khairnar et al, 2019; Oh & Lee, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Self-efficacy is essential for improving glycaemic control (Khairnar et al, 2019;Oh & Lee, 2017) and subjective health status (Bishwajit et al, 2017;Jung et al, 2015;Park, 2010) • Diabetes management self-efficacy had significant indirect effects on subjective health status via diabetes selfcare activities and HbA1c and was an important factor through which diabetes knowledge, psychological insulin resistance and diabetes management family support had an indirect effect on subjective health status.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…() asserted that each self‐care behavior needs to be measured and scored separately, rather than combining scores across behaviors. Nevertheless, many of the previous studies have explored diabetes self‐care behaviors using only a combined score for all of the considered behaviors (Eyüboğlu & Schulz, ; Oh & Lee, ; Wang et al., ; Yamashita & Kart, ), which made it difficult to obtain information about each self‐care behavior. In contrast, the present study investigated how each self‐care behavior was individually related with health literacy and empowerment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have applied empowerment strategies to chronic diseases, such as chronic renal failure and rheumatoid arthritis, and have succeeded in self-care and symptom management [ 5 , 34 , 35 , 36 , 37 ]. According to ADA guidelines, diabetes self-management education and support should be patient-centered and provided in group or personalized settings [ 30 ].…”
Section: Discussionmentioning
confidence: 99%